Experimental Identification of Cracking Parameters of Concrete Ties with Different Reinforcement and Testing Layouts. (2017) - Rimkus, Arvydas; Jakstaite, Ruta; Kupliauskas, Rimantas; Torres, Lluis; Gribniak, Viktor
Abstract: Despite a seeming simplicity of the direct tensile test layout, analysis of sources of scatter of the experimental results on cracking and deformations of reinforced concrete ties inspired the authors to investigate representativeness of the specimens. In the current context, the representativeness is understood as a property of the tie to isolate the investigated parameter (e.g., cracking deformations) from others uncontrolled effects characteristic for the samples of limited size. The present experimental study aims at determination of representative length of the samples that allows reduce the end effect. A consistent procedure is proposed for identification of the cracking parameters in the cases of limited capability of monitoring deformations of internal reinforcement. The proposed procedure was applied for the cracking analysis of concrete prisms with different reinforcement and testing layouts.